Entangled Intimacies: An Experimental Curatorial Project of Transdisciplinary Becoming-With - Thomas, Rory Lee Stewart (University of the Witwatersrand, Johannesburg, 2023)
Employing strategic modes of textual and curatorial “opacity” (Glissant 1997: 189), this project endeavours to consider how arts-based research methodologies may be uniquely positioned to explore the chaotic embodied implications of the so-called Anthropocene. This work of arts-based knowledge production and explorative enquiry is centred around an exhibition I have curated entitled Entangled Intimacies: art, more-than-human embodiment, and the climate catastrophe, which constitutes this project’s practical component. The exhibition is being held from 10 February to 6 May 2023 at the Goethe-Institut Johannesburg gallery and features newly commissioned artworks by local practitioners Tzung-Hui Lauren Lee, Io Makandal, and Natalie Paneng. This research report considers the ongoing process of curating this exhibition via a varied textual pathway that follows through a number of different considerations and references. These include an assessment of individual and collective grief, the potential of utilising curatorial opacity as a means of relating to the chaos of ecological degradation, and a discussion of a selection of previous curatorial projects from the last two decades which have engaged this reality through contemporary art. These projects include DON’T/PANIC (2011), Sex Ecologies (2021-2022), and the ongoing work of Johannesburg based not-for-profit arts organisation POOL (founded in 2015). The diverse, and at times perhaps disorientating, form of this research report is a curatorial and written reflection on the chaotic implications of more-than-human embodiment in the Anthropocene. This is conceived as an actualisation of curator Stefanie Hessler’s (2020: 249) assertion that “[t]he uneven, uncontainable climate crisis obligates curators to rethink ways of working. Exhibition making in times of ecological disaster … needs to differ from previous curatorial modes.” This project works to remain aware of the city of Johannesburg as its site of emergence while also engaging with the globally interconnected reality of the Anthropocene. It thus offers a propositional, mutable, and exploratory gesture towards what contemporary curatorial practice within this uncertain time and place marked by ecological violence may entail.
A research project submitted in partial fulfilment of the requirements for the degree of Master of Arts in Contemporary Curatorial Practice in the History of Art department, Wits School of Arts, Faculty of Humanities, at the University of the Witwatersrand, Johannesburg, 2023.
Keywords: Curatorial Studies; Contemporary Art; Curatorial Practice; Ecology; Anthropocene; Ecological Degradation; Opacity; Becoming-With; Uncertainty; Death; Loss; Interconnection; Transdisciplinary; Entanglement; Embodiment; UCTD; SDG-4: Quality education